Kaizen internal quality assurance adoption and quality performance improvement in Indonesian higher education institutions: The moderating role of IT development - Hafiez Sofyani (Journal of Accounting and Investment, 2023)
Research aims: In 2018, strengthening Higher Education Institutions (HEIs), governance began to be promoted again by the Indonesian government after its first initiation in 2003. In doing so, the Indonesian government has adopted a new internal quality assurance framework for HEIs, i.e., the Kaizen method, which emphasizes the quality improvement process. In addition, the government recommended the development of IT advancement to support management practices at the HEIs, including internal quality assurance. However, to this day, related research that examines the extent to which these policies contribute to HEI quality performance improvement still needs to be improved. To meet the gap, the current study examined the Kaizen internal quality assurance implementation role on HEI quality performance by testing the IT development as a moderator.Design/Methodology/Approach: Using data from 191 HEI samples obtained from 31 of 34 provinces in Indonesia, the relationship between variables was tested by employing the Partial Least Square (PLS) technique.Research findings: The results exhibited that the Kaizen internal quality assurance implementation was positively associated with HEI quality performance, where IT development strengthened the relationship (moderated). However, since the direct relationship between IT development and HEI quality performance was also significant, the moderating role of IT development was quasi in nature.Theoretical contribution/Originality: The results provide new insights regarding the contributions of internal quality assurance reform supported by IT development to the HEI quality performance. Specifically, the study affirms the role of IT as a moderator.